Die Erforschung der Luxemburger Wortbildung als Aufgabe. Eine Projektvorstellung - Sieburg, Heinz; Weimann, Britta (Linguistik Online, 2016)
Research on Luxembourgish word formation – both from a historical and a synchronic perspective – is still at its very beginning. Its most challenging aspect is the complex multilingual situation in Luxembourg which arose due to the country’s intricate history. The research project “WBLUX” takes this unique situation into account; It has been designed as a multi-stage corpus-based tandem project as a cooperation between German and Luxembourgish studies. This paper commences by introducing the project design and the corpus concept, followed by a presentation of some exemplary corpus data.